The Determination of Serum Fibrinolytic Inhibitors in Normal Practice - Daver, J; Albugues, M. J; Pasquier, J. P. Du; Ricoeur, M (Thrombosis and Haemostasis, 1969)
It is desirable that every biology laboratory should be able to carry out the determination of serum fibrinolytic inhibitors. Two simple techniques which can be easily performed have been studied.The first consists in measuring the lysis surface, using an activator, (plasmin) of a fibrin plate, to which the inhibitors are added in the form of a 1/10th concentration of the serum to be studied, using Blix’s method.The second is the measuring of a standard fibrin clot, activated by streptokinase, in the presence of added inhibitors in the form of a 1/10th concentration of the serum to be studied, using Hawkey’s method.The measurements taken by double determination with these two techniques on the sera of 569 subjects during epidemiological research on atherosclerosis, have shown that they do not measure the same thing, and it is not possible to give an explanation. However it is possible to make some assumptions.